Chelonian type specimens at the Oxford University Museum - Nowak-Kemp, Małgosia; Fritz, Uwe (Zootaxa, 2010)
In the present paper, the history of the chelonian collection of the Oxford University Museum is summarized and extant type specimens are identified. Currently, there are 46 name-bearing types of 25 chelonian taxa and paralectotypes of three taxa described by Georg Baur, Thomas Bell, André Marie Constant Duméril & Gabriel Bibron, and John Edward Gray from the families Emydidae, Geoemydidae, Testudinidae, Chelidae, and Pelomedusidae. Among the name-bearing types, there are holotypes of eight taxa (Cyclemys bellii Gray, 1863; Emys speciosa var. levigata Gray, 1831; Phrynops bellii Gray, 1844; Rhinoclemys bellii Gray, 1863; Sternothaerus leachianus Bell, 1825; Sternothaerus trifasciatus Bell, 1825; Testudo hercules var. truncata Gray, 1831; Testudo tentoria Bell, 1828) and one lectotype is of Pyxis arachnoides Bell, 1827. Two additional holotypes or syntypes are of Terrapene maculata Bell, 1825 and Terrapene nebulosa Bell, 1825, and 35 syntypes represent 14 taxa (Cyclemys orbiculata Bell, 1834; Emys concentrica var. polita Gray, 1831; Emys crassicollis Gray, 1831; Emys decussata Gray, 1831; Emys hamiltonii Gray, 1831; Emys irrigata Duméril & Bibron, 1835; Emys speciosa Gray, 1831; Emys spinosa Gray, 1831; Emys tectum Gray, 1830; Emys thurjii Gray, 1831; Kinixys castanea Bell, 1827; Kinixys homeana Bell, 1827; Testudo actinodes Bell, 1828; Testudo guntheri Baur, 1889). Three paralectotypes are of Emys dentata Gray, 1831, eight paralectotypes are of Emys vulgaris Gray, 1831, and one paralectotype is of Pyxis arachnoides Bell, 1827. Except the syntype of Testudo guntheri Baur, 1889, originating from the college of Christ Church, Oxford, all type specimens belong to the former collection of Thomas Bell that was transferred to Oxford in 1862. Testudo guntheri Baur, 1889 is regarded as nomen dubium because it was based on specimens without locality data.